Perdebatan Realisme-Antirealisme dalam Filsafat Agama Kontemporer - Khasri, Muhammad Rodinal Khair; Fuad Abdullah Harahap (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2023)
This article starts from the ontological problem in the discourse on the philosophy of religion, namely between the realist and anti-realist poles. The two are differentiated from the way of understanding the world, where realists believe that there is a world that is independent of mind and consciousness (mind-independent world) while anti-realists believe that the world, including perspectives on it, is completely dependent on the intentionality of the subject, so it is only a construction of mind and consciousness. Regarding religion, for realists, religion and its substance truly refer to objective reality, while anti-realists believe that religion is fictitious because it is only a construction of the mind and consciousness, not referring to objective reality. This debate also implies a disagreement between theism and atheism, especially in the context of the ontological status of religion and the epistemic status of religion. This article wants to explain that a believer is definitely a realist. This realist attitude is confirmed through an ontological commitment to the existence of God. However, the semantic construction of divinity is in the domain of mind and consciousness. The object of representation exists in a world independent of the mind, while the content of the representation exists within the influence and determination of the mind. This has consequences for the subject's plurality of meanings of the world. Regarding the theism-atheism dialogue pattern, this article offers a more analytical dialogue pattern, namely dialogue that is not theologically centric. This means that the debate is more directed at how to talk about God, not just about God's existence.